Experimental Evaluation of Phase Change Material Blister Panels for Building Application (Future Cities and Environment, 2020)
Phase Change Materials (PCMs) are characterised by their capacity to absorb available thermal energy, store it, and passively release it by utilizing latent heat during phase change, thus reducing temperature peaks and improving thermal comfort. This paper experimentally investigates the feasibility of a novel blister PCM panel for ceiling tile applications. Experimental panels enhance the thermal conductivity of the PCM with the addition of steel and aluminium wool particles at 3.77 wt.% and 23 wt.%, respectively. During the experimental procedure, the blister panels where able to absorb the heat coming from the environmental chamber, proving that the encapsulation material was able to promote the heat exchange. Furthermore, the PCM enhancement indicates that both the aluminium and steel wool particles improved the blister panel thermal performance. These results were confirmed by thermal conductive, calculated at 0.733 W/(m K) for the base panel, 0.739 W/(m K) for the aluminium wool, and 0.784 W/W/(m K) for the steel wool. The experiment suggest that the application of PCM blister ceiling tiles can be considered as an innovative method for thermal performance control and energy saving.